Expanding the role of community hospitals to promote population health in Singapore - Ken Wah Teo; Lian Leng Low; Wee Hoe Gan; Luke Sher Guan Low; Chien Earn Lee (The Lancet Regional Health. Western Pacific)
Summary: Population health encompasses health outcomes, their determinants, and the distribution within the group of individuals. A life course approach, involving residents regardless of health status and disease complexity, and addressing their needs holistically and contextually is a key policy for improving population health. Healthier SG represents Singapore’s transformation towards population health. Under this initiative, Singapore’s three healthcare clusters have been tasked with new roles as population health managers and regional health managers, on top of being healthcare service providers. We propose that beyond intermediate and post-acute care, community hospitals, as service providers, have an opportunity to (a) innovate new models of integrated and appropriate care, (b) adopt life-course approaches which include prevention and end-of-life care extended to community settings, (c) strengthen person-centred and holistic care approaches through social prescribing, (d) lead capability building and sector development for person-centred care, and (e) galvanize the health-social care ecosystem.